Film Discourse: the semiotic and nature - Erkaeva , Dilnoza (The Lingua Spectrum, 2025)
In this article, the critical, cultural, and creative features of American and Uzbek cinematic discourse, as well as the intercultural analysis, are discussed. The focus of the research is on introducing the meta-discursive category of communicative role exchange, which is described as "...a system of strategies, tactics, and techniques that manage the dialogic communication process using verbal or non-verbal speech, with the potential to point to a transitional point or relevant turning point, accepting, maintaining, or transferring the right to voice entry to one of the participants in the interaction." The structurally regulating meta-discursive feature of this system is manifested in its inclusion. There are specific tactics and methods for changing the nature and roles in relation to other discursive categories.